DESKRIPSI PENYELESAIAN MASALAH ALJABAR BERDASARKAN TAKSONOMI SOLO DITINJAU DARI KEMAMPUAN AWAL DAN GAYA BELAJAR SISWA KELAS VIII SMP NEGERI 14 AMBON - Syafruddin Kaliky (MATEMATIKA DAN PEMBELAJARAN, 2016)
The study aimed at describing problem solving on algebra based on SOLO taxonomy viewed from initial ability and learning style of grade VIII students of SMP (junior high school). The study was descriptive with qualitative approach which used the researcher as the main instrument; whereas the supporting instruments were test of initial ability, questionnaire of learning style, test of problem solving on Algebra, and guided interview. Test of initial ability used was limited to high initial ability and low initial ability. Whereas, learning style consists of visual learning style, auditory and kinesthetic. The results of the study revealed that students solving Algebra problem based on the fulfillment of SOLO taxonomy indicators, namely the first subject with high initial ability and visual learning style tended to achieve extended abstract level; whereas, the second subject tended to achieve relational level. Subject with high initial ability and auditoria learning style tended to achieve relational level. Subject with high initial ability and kinesthetic learning style tended to achieve extended abstract level. Subject with low initial ability and visual learning style tended to achieve multistruktural level. Subject with low initial ability and auditoria learning style tended to achieve transition period at multistruktural level. Subjek with low initial ability and kinesthetic learning style tended to achieve multistructural level. Key Words: Problem Solving Based on SOLO Taxonomy, Initial Ability and Learning Style